Coping with change in India’s media: Struggles of English-language journalists in an evolving mediascape - Levi Obijiofor (Asia Pacific Network, 2020)
In recent times, journalism, worldwide, has been undergoing significant changes. Some of the major revolutions have occurred in India, the world’s largest democracy. The size and face of Indian news media have seen rapid transformations owing to major economic, technological, and political developments in the country in recent decades. The focus of this research is on how India’s English-language media are dealing with the various changes, including digital disruptions and other pressures under Prime Minister Narendra Modi’s ‘Hindutva’ government. The insights are drawn from the experiences and perceptions of a sample of journalists at the forefront of covering major events. Being in the coalface, these journalists are bearing the brunt of the developments, both good and bad. The email interviews reveal that while the English-language media may be a small part of India’s vast national media landscape, they are also buffeted by some major developments in the country, and fighting to maintain their independence in the face of some powerful trends and influences in technology, politics, and commerce.